The techniques of memorization music pieces : a case study of students Faculty of Music Shah Alam / Mohd Rizal Mohd Mansha - Mohd Mansha, Mohd Rizal (2013)
This study was conduct to explore techniques of memorization music piece a case study UiTM faculty of music Shah Alam . The purpose of this study to identify how music students perceive the important memorizing, to find out the best way for memorizing the music piece and to identify the benefits of memorizing techniques. For this particular study, this study will use the quantitative method in order to gather opinions from a large group of the student in UiTM needed regarding the specific topic of this study.